Beispiel Nr: 06
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 7x +1\frac{1}{2}y =1\\ 2x -5y = 22 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 7 x +1\frac{1}{2} y =1\\ II \qquad 2 x -5 y = 22 \\ \text{I nach x auflösen}\\ 7 x +1\frac{1}{2} y =1 \\ 7 x +1\frac{1}{2} y =1 \qquad /-1\frac{1}{2} y\\ 7 x =1 -1\frac{1}{2} y \qquad /:7 \\ x =\frac{1}{7} -\frac{3}{14} y \\ \text{I in II}\\ 2 (\frac{1}{7} -\frac{3}{14} y ) + -5 y = 22 \\ \frac{2}{7} -\frac{3}{7} y -5 y = 22 \qquad / -\frac{2}{7} \\ -\frac{3}{7} y -5 y = 22 -\frac{2}{7} \\ -5\frac{3}{7} y = 21\frac{5}{7} \qquad /:\left(-5\frac{3}{7}\right) \\ y = \frac{21\frac{5}{7}}{-5\frac{3}{7}} \\ y=-4 \\ x =\frac{1}{7} -\frac{3}{14} y \\ x =\frac{1}{7} -\frac{3}{14} \cdot \left(-4\right) \\ x=1 \\ L=\{1/-4\} \end{array} & \begin{array}{l} I \qquad 7 x +1\frac{1}{2} y =1\\ II \qquad 2 x -5 y = 22 \\ \text{I nach y auflösen}\\ 7 x +1\frac{1}{2} y =1 \\ 7 x +1\frac{1}{2} y =1 \qquad /-7 x\\ 1\frac{1}{2} y =1 -7x \qquad /:1\frac{1}{2} \\ y =\frac{2}{3} -4\frac{2}{3}x \\ \text{I in II}\\ 2x + -5(\frac{2}{3} -4\frac{2}{3} x ) = 22 \\ -3\frac{1}{3} +23\frac{1}{3} x -5 x = 22 \qquad / -\left(-3\frac{1}{3}\right) \\ +23\frac{1}{3} x -5 x = 22 -\left(-3\frac{1}{3}\right) \\ 25\frac{1}{3} x = 25\frac{1}{3} \qquad /:25\frac{1}{3} \\ x = \frac{25\frac{1}{3}}{25\frac{1}{3}} \\ x=1 \\ y =\frac{2}{3} -4\frac{2}{3} x \\ y =\frac{2}{3} -4\frac{2}{3} \cdot 1 \\ y=-4 \\ L=\{1/-4\} \end{array} \end{array} $